BUNUH DIRI DI BALI: PERSPEKTIF BUDAYA DAN LINGKUNGAN HI - Widnya, I Ketut (Bumi Lestari; Vol 8 No 1 (2008), 2012)
Abstract Bali is one of island in Indonesia that cannot avoid itself from domino effect of suicide as caused by modernization. The rate of suicide in Bali is improving year by year in associate with Balinese society that modernized themselves. The changing of culture environment and degradation of environment give a potential contribution toward the rising the suicide rate in Bali. This geographically correlated and countryside are where the suicide case frequently occurred. From the culture aspect, these countryside are not strong enough to do resistance toward social and cultural transformation caused by modernization. Whereas from the environmental aspect, the degradation of environmental quality in those and areas, causes economical depression and in suicide. For Bali Island that has a unique environmental potency and noble culture modality ? so that it is called Paradise Island ? the phenomenon of suicides is an extra ordinary because it has happened a tragic cultural tragedy in Bali. It is paradox because suicide is an anti climax of divine ideal that should be established in this the island of Paradise.
Keywords: Key word: suicide in Bali, cultural and environmental perspective